PENERIMAAN SISTEM E-LEARNING MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL (TAM) STUDY KASUS SISWA/I KELAS X DI SMU NEGERI 92 JAKARTA - Oktofiyani, Rini; Nurmalasari, Nurmalasari; Anggraeni, Wakhyu (Jurnal Pilar Nusa Mandiri, 2016)
The current technology developments led to the need for information quickly, precisely and accurately. One of the technological developments in the field of education is the elearning. SMA Negeri 92 Jakarta is one of the implemented system learning who made online and are expected to help students improve their learning. Instruments research on analysis of acceptance e-learning systems using technology Acceptance Model (TAM) is the questionnaire form and the object of research is the grade X SMA Negeri 92 Jakarta 138 respondent of the student taken. Analysis of the data done by the descriptive analysys techniques using the categories and percentages through the scale likert. The result showed that the relationship between variable X (Perceived Ease Of Use and Perceived Usefulness) and variable Y (behavioral Intention to Use) in acceptance system e-learning SMA Negeri 92 Jakarta is 0,727. The value of the correlation of this very strong positive. The relationship has a positive is the direct relationship between variable X and Variable Y.